A Look at the World through a Word Shoes: A Componential Analysis of Meaning - Miftahush Shalihah (Journal of Language and Literature, 2015)
Meanings are related to language functions. To comprehend how the meanings of a word are various, conducting componential analysis is necessary to do. A word can share similar features to their synonymous words. To reach the previous goal, componential analysis enables us to find out how words are used in their contexts and what features those words are made up. Shoes is a word which has many synonyms as this kind of outfit has developed in terms of its shape, which is obviously seen. From the observation done in this research, there are 26 kinds of shoes with 36 distinctive features. The types of shoes found are boots, brogues, cleats, clogs, espadrilles, flip-flops, galoshes, heels, kamiks, loafers, Mary Janes, moccasins, mules, oxfords, pumps, rollerblades, sandals, skates, slides, sling-backs, slippers, sneakers, swim fins, valenki, waders and wedge. The distinctive features of the word shoes are based on the heels, heels shape, gender, the types of the toes, the occasions to wear the footwear, the place to wear the footwear, the material, the accessories of the footwear, the model of the back of the shoes and the cut of the shoes.Keywords: shoes, meanings, features